Islamic Art and Architecture: A Systematic Review of Aesthetics, Symbolism, and Cultural Significance - Chosinawarotin Chosinawarotin (Penelitian dan Pengembangan Ilmu, 2024)
Islamic art and architecture is a rich expression that reflects a close connection with Islamic aesthetic values, symbolism and cultural heritage. This research aims to understand the evolution of symbolism in Islamic art and architecture, as well as how this symbolism influences aesthetic perceptions and cultural meaning throughout history and in various geographic regions. Using the PRISMA method to select articles from various international databases, this study analyzes the transformation of symbolism in a dynamic historical and cultural context. The research results show that symbolism in Islamic art not only functions as a decorative element but also as a medium for conveying cultural identity, religious values, and regional variations. This research provides new insights that enrich understanding of Islamic art and architecture and its implications for cultural studies more broadly.